Inovasi Penguatan Literasi Digital di Kalangan Remaja Kota Tasikmalaya Dalam Mendukung Capaian SDGS 2030 - Fitrah Arya Ramadhan; Yuda Amri Setiadi; Ichsan Rahman Fauzi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Digital Education or Digital Literacy is one of the main keys to preparing future generations who will never escape the involvement of modern devices or gadgets, in order to educate the generation in facing the challenges of global change. Tasikmalaya is one of the regions and cities that is attractive for teenagers to be the subject of achieving SDGS or in Indonesian